The Importance Of Wise-Consumption Internalization For Elementary School Children - Silky Roudhotus Sa’adah; Budi Eko Soetjipto; Ery Tri Djatmika Rudijanto (CV. AFDIFAL MAJU BERKAH, 2022)
Wise – consumption can be defined as frugality by using goods sufficiently and not excessive. Wise behavior is the implication of frugal activity concerning available resources distribution. This research aims to describe how to internalize wise – consumption to elementary school children, and to familiarize the children about what good consumption activity is. This research is qualitative research with phenomenological studies approaches in Siraman, Kesamben, Blitar Regency. The subject of this research is 30 families that have elementary school children. Moreover, data analysis used a technique of descriptive qualitative. The research finding shows that internalization can be conducted by exemplary, verbal explanation, and habitual relevant action.